2018
DOI: 10.1016/j.jmb.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Anti-Tumor Opsonizing Proteins with Fibronectin Scaffolds Engineered for Specificity to Each of the Murine FcγR Types

Abstract: We have engineered a panel of novel Fn3 scaffold-based proteins that bind with high specificity and affinity to each of the individual mouse Fcγ receptors (mFcγR). These binders were expressed as fusions to anti-tumor antigen single-chain antibodies and mouse serum albumin, creating opsonizing agents that invoke only a single mFcγR response rather than the broader activity of natural Fc isotypes, as well as all previously reported Fc mutants. This panel isolated the capability of each of the four mFcγRs to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…To our knowledge, this is the first report of an FcγRIV-specific VHH. A fibronectin scaffold protein that could specifically bind to FcγRIV with high affinity has been reported (63). In addition, this scaffold protein was able to delay tumor growth in a mouse model when linked to an anti-tumor antigen-specific single-chain antibody and mouse serum albumin (to extend the half-life of the fusion construct).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of an FcγRIV-specific VHH. A fibronectin scaffold protein that could specifically bind to FcγRIV with high affinity has been reported (63). In addition, this scaffold protein was able to delay tumor growth in a mouse model when linked to an anti-tumor antigen-specific single-chain antibody and mouse serum albumin (to extend the half-life of the fusion construct).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-specific mAbs can help to bypass the anti-phagocytic signals by targeting tumor cells and interacting with macrophage FcγR to cause ADCP [158] (Figure 4a). The potential of four mFcγRs to support macrophage phagocytosis of opsonized tumor cells and tumor growth suppression in vivo was proven by Chen et al The results showed that while activating receptors (mFcγRI, mFcγRIII, and mFcγRIV) were equally capable of triggering specific tumor cell phagocytosis, the inhibitory receptor mFcγRII was unable to do so [159]. Some "don't eat me" signal blockades, such as RF231(a fully human anti-CD47), can not only promote CD47-mediated death signaling in tumor cells but also triggers FcγR-mediated phagocytosis of tumor cells [98].…”
Section: Adcp-potentiating Agentsmentioning
confidence: 99%
“…Protein scaffolds are a wide research focus because they can be used as antibody replacement therapy [32][33][34][35]. Scaffold-based specific peptides are usually developed by using display technologies, such as phage, yeast, or ribosome/mRNA displays [36].…”
Section: Discussionmentioning
confidence: 99%